Pendidikan Karakter Melalui Metode Pembelajaran Field Trip Di Tk Kusuma Mulia Sugihwaras Purwoasri Kediri - Farhan, Margiati (Inovasi: Jurnal Diklat Keagamaan, 2021)
This Paper discusses: (1) the importance of planting efforts character in early childhood in early childhood institutions; (2) the learning activities a Field Trip that reflect the application of character education in early childhood institutions; and (3) the variety of characters who woke up as the effects of the application of the learning Field Trip in early childhood in early childhood institutions. Character education involves the planting of knowledge, the love and the planting of the behavior of the kindness that become a pattern/habit. The purpose of this study is to determine the success and impact of the use of learning methods Field Trip. The method used is to observe the activities of the Field Trip that reflect the character education for early childhood, among others, is a visit to the neighborhood, to a tourist place, to market, to shop, to an industry, to the boarding school, to school, to the hospital, as well as other places nearby with the environment agency.